Computational study of entropy on superconductors - Ng, Jin Quan (2016)
The focus of this paper is to establish the behaviour of a new class of recently discovered (2006) iron based superconductors under the framework of Density Functional Theory (DFT). In particular, this study aims to study the behaviour of sulphur doped iron(II) telluride as it undergoes the superconducting phase transition. This is done by studying the electronic entropy above and below the critical temperature. Interesting results have been obtained which could be used to study superconductivity further.